The Middle to Upper Paleolithic transition in the southern Levant: New insights from the late Middle Paleolithic site of Far'ah II, Israel. (1st June 2020) - Goder-Goldberger, Mae; Crouvi, Onn; Caracuta, Valentina; Kolska Horwitz, Liora; Neumann, Frank H.; Porat, Naomi; Scott, Louis; Shavit, Roi; Jacoby-Glass, Yael; Zilberman, Tami; Boaretto, Elisabetta
Abstract: Far'ah II is an open-air site in the north western Negev desert (Israel). Previous excavations in the 1970's revealed a rich, in situ Middle Paleolithic (MP) assemblage composed of flint and limestone artifacts, animal bones and charcoal. Renewed excavation at the site were undertaken in 2017, to re-date it and provide a more accurate constrain to the sites' age, as well as collect samples for paleoclimatic proxies. Our new Optically Stimulated Luminescence and 14 C ages together with the stable oxygen isotope signature of the loess sediments, constrain the age of the upper archaeological horizon to <49 ka. This age agrees with the younger limit of 60–50 ka, obtained by Electron Spin Resonance ages, measured in the 1990's. The heavy δ 18 O values in carbonates point to cooler climatic conditions than those that prevailed during the preceding short, warm episode between 58 and 49 ka. The fauna, pollen and charcoal collected during the excavation portray a savanna-like environment with a mix of Irano-Turanian and Saharo-Arabian elements and a minor Mediterranean component. The lithic assemblage exhibits large technological variability typical of the Late MP (LMP), amongst which are technological traits that are clearly present in the Initial Upper Paleolithic (IUP) assemblages at the nearby, and roughly contemporaneous, site of Boker Tachtit. If population replacement was the trigger to the MP-UP transition, we would have expected to see a clear break in the cultural material at the onset of the Upper Paleolithic. The semi-arid north western Negev, as an interim region between the Mediterranean and Saharo-Arabian ecozones could have facilitated interaction between populations moving north or south due to fluctuating climatic conditions and changes in population pressures, possibly leading to the emergence of new technological traditions that are observed in the later UP. Highlights: Combining 14 C and OSL dating with stable isotope analysis the age of Far'ah II is constrained to < 49 ka. Late MP technological variability at Far'ah II displays traits present in IUP assemblages. Fauna, pollen and charcoal collected portray an open semi-arid environment. Heavy δ 18 O values in carbonates point to cooler climatic conditions.